Applications of advanced machine intelligence in computer vision and object recognition emerging research and opportunities - Chakraborty, Shouvik, 1992-; Mali, Kalyani, 1962- (Advances in computational intelligence and robotics (ACIR) book series., 2020)
"This book explores recent developments and advancements in object recognition using artificial intelligence"--